2002
DOI: 10.1002/ecjb.10030
|View full text |Cite
|
Sign up to set email alerts
|

Surface passivation of epitaxial multilayer structures for InP‐based high‐speed devices by an ultrathin silicon layer

Abstract: SUMMARYA novel method for surface passivation of epitaxial multilayer structures for InP-based high-speed devices by an ultrathin silicon interface control layer (Si ICL) is discussed. Theoretical design and optimization of the surface passivation structure with and without an InGaAs cap layer is performed by taking account of the strain effect and quantized states in the Si ICL. Then the formation process of a SiN x /Si ICL structure utilizing a novel partial-nitridation technique is optimized. It is clarifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2004
2004
2004
2004

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…The increase of the capacitance at high frequencies looks insufficient. However, as Xie et al have demonstrated theoretically [14], even if the high frequency capacitance is increased sufficiently, this may be due to a parasitic effect of an area ( mm, in our MIS diode samples) between a broad Ohmic contact and the MIS junction (0.32 mm diameter).…”
Section: Effects Of Nitrogen Plasmamentioning
confidence: 67%
See 1 more Smart Citation
“…The increase of the capacitance at high frequencies looks insufficient. However, as Xie et al have demonstrated theoretically [14], even if the high frequency capacitance is increased sufficiently, this may be due to a parasitic effect of an area ( mm, in our MIS diode samples) between a broad Ohmic contact and the MIS junction (0.32 mm diameter).…”
Section: Effects Of Nitrogen Plasmamentioning
confidence: 67%
“…2, where the capacitance of the nitrided MIS diode is nearly equal to that of the simply oxidized MIS diode in the high-frequency region (1 MHz). However, this contradiction is explained by the theory developed by Xie et al [14]; the parasitic effect of the area between the MIS junction and the Ohmic contact of the MISFET is very small compared to that of the MIS diode ( mm), and thus the increase in capacitance by nitridation is observed directly in the FET. Nitridation increases both the transconductance and the capacitance, but the remains unchanged.…”
Section: DC Characteristicsmentioning
confidence: 99%